Pengaruh Matakuliah Kewirausahaan terhadap Minat Mahasiswa Menjadi Wirausaha - Sri Aderafika Sani; Zuhrinal M. Nawawi (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The Entrepreneurship course aims to make students learn to understand entrepreneurship, learn to have an entrepreneurial spirit, and learn to be an entrepreneur. This type of research is quantitative research. This study aims to determine the effectiveness of Entrepreneurship courses in order to increase student interest in entrepreneurship by using multiple regression tests to compare the interests of students who take entrepreneurship courses with those who do not take entrepreneurship courses. In semesters 2, 4, and 6, 30 random samples were obtained for each group of students. The results obtained indicate that the implementation of entrepreneurship courses affects student interest in entrepreneurship. For 2nd semester students they do not take entrepreneurial decisions, but they do take them in high school. On the other hand, 4th semester students are interested in jobs that can guarantee a steady income (job). The results of this study can explain the need for students to accompany the offering of entrepreneurship courses in more practical applications in order to gain a clearer understanding of entrepreneurship. Keywords: Entrepreneurship, Entrepreneurship Course, Interest in Entrepreneurship